Wavelet transform analysis of dynamic speckle patterns texture - Limia, Margarita Fernández (2002)
We propose the use of th wavelets transform to characterize the time evolution of dynamic speckle patterns. We descibe it with an example for the assessment of drying of paint. Optimal texture features are determined and the time evolution is described in terms of tha Mahalanobis distance from the final (dry) state.